1993
DOI: 10.1007/bf02918992
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic acid chelators in manganese regulation of lignin degradation byPhanerochaete chrysosporium

Abstract: Nitrogen, carbon, and manganese are potent regulators of lignin degradation, but although nitrogen and carbon elicit a generalizated response when cells are starved, manganese is a relatively specific regulator of lignin and manganese peroxidase (LiP and MnP, respectively). At high manganese levels, MnP is induced, and LiP is repressed. At low Mn levels, MnP is repressed, and LiP is induced. Organic acid chelators are very important in attaining LiP repression with high Mn. Both mineralization and lignin depol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 25 publications
1
55
1
Order By: Relevance
“…Culture studies with lignindecomposing fungi showed that trivalent Mn 3+ is generated during the oxidation of lignin model compounds (17). It has been proposed that Mn 3+ is formed via the oxidation of soluble Mn 2+ by fungal exo-enzymes, such as Mn peroxidase or phenol oxidases (e.g., laccase).…”
mentioning
confidence: 99%
“…Culture studies with lignindecomposing fungi showed that trivalent Mn 3+ is generated during the oxidation of lignin model compounds (17). It has been proposed that Mn 3+ is formed via the oxidation of soluble Mn 2+ by fungal exo-enzymes, such as Mn peroxidase or phenol oxidases (e.g., laccase).…”
mentioning
confidence: 99%
“…Therefore, it is possible that manganese also regulates the overall mineralisation of target compounds like persistent recalcitrant chemicals and in this case, Aroclor (Bonnarme and Jeffries, 1990). Perez and Jeffries (1992) and Kern (1989Kern ( , 1990, also found that Mn(II) induced MnP and that simultaneous repression of LiP was due to the presence of soluble complexes of simple organic acids. The higher concentrations of Mn ions, provided by solid Mn0 2 , indicated a higher production of MnP in our study for all trials, excepting the culture containing 57.5 mM Mn0 2 .…”
Section: Aroclor Biodegradationmentioning
confidence: 83%
“…Although additions of Mn# + might be expected to accelerate the decoloration of dyes, the presence of 0n2 m Mn# + in HRP solution and soybean root extract inhibited the enzymic reactions of plant peroxidase. Inhibition by Mn# + has also been reported for the lignin peroxidase of Phanerochaete chrysosporium Burdsall (Perez & Jeffries, 1992). The nature of this inhibitory effect on certain peroxidases is unknown.…”
Section: mentioning
confidence: 92%